2013
DOI: 10.1097/jnr.0b013e3182828d77
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Psychosocial Factors for Dyspnea in Taiwanese and American Heart Failure Patients

Abstract: Depression, anxiety, and perceived social support moderated the relationship of clinical characteristics with dyspnea in Taiwanese and American HF patients, respectively. Attention to these psychosocial factors may improve dyspnea status in HF patients. Symptom management should include a focus on patients' psychological distress and social perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…35,36 Depressive symptoms were identified as an influencing factor of dyspnea in our study, which agreed with reports from a recent study. 37 The findings in the current study show that psychological as well as physiological factors are associated with dyspnea.…”
Section: Discussionsupporting
confidence: 50%
“…35,36 Depressive symptoms were identified as an influencing factor of dyspnea in our study, which agreed with reports from a recent study. 37 The findings in the current study show that psychological as well as physiological factors are associated with dyspnea.…”
Section: Discussionsupporting
confidence: 50%
“…Depression and anxiety are major comorbidities in respiratory disease, cardiac disease and cancer [45–49]. Depression and anxiety are associated with increased breathlessness [50,51], increased mortality (depression is associated with almost doubled mortality over 1 year [30]) [52,53], a 10% increase in hospitalizations and diminished social and physical functioning (anxiety and depression are associated with a 13.7 point difference on the impact scale of the St George's Respiratory Questionnaire, on which 4 points is the minimally clinically important difference [54]) [23]. Furthermore, neuroimaging studies of breathlessness perception have identified activity in brain areas regularly associated with emotion and affective processing including the anterior cingulate cortex, insula and amygdala, as well as sensory processing areas [15,16,37,5559].…”
Section: Influences On Breathlessness Perceptionmentioning
confidence: 99%
“…Furthermore, not all scales have an established minimal clinically important difference PLOS ONE [23] and it may be difficult to capture a meaningful change in dyspnea with the current scales available [4,5]. Finally, psychological and emotional distress has been significantly associated with dyspnea in HF [24,25] but these components or alterations of sensorial quality are usually nor assessed in the most commonly scales used for dyspnea assessment [6]. Accordingly, it is not surprising that many HF drug studies that have dyspnea relief as end points have failed to show a difference between the active drug and placebo.…”
Section: Discussionmentioning
confidence: 99%